Universal immunity to influenza must outwit immune evasion - Quiñones-Parra, Sergio; Loh, Liyen; Brown, Lorena E.; Kedzierska, Katherine; Valkenburg, Sophie A. (Frontiers in Microbiology, 2014)
Although an influenza vaccine has been available for 70 years, influenza virus still causes seasonal epidemics and worldwide pandemics. Currently available vaccines elicit strain-specific antibody responses to the surface haemagglutinin (HA) and neuraminidase (NA) proteins, but these can be ineffective against serologically-distinct viral variants and novel subtypes. Thus, there is a need for cross-protective or “universal” influenza vaccines to overcome the necessity for annual immunisation against seasonal influenza and to provide immunity to reduce the severity of infection with pandemic or outbreak viruses. It is well established that natural influenza infection can provide cross-reactive immunity that can reduce the impact of infection with distinct influenza type A strains and subtypes, including H1N1, H3N2, H2N2, H5N1 and H7N9. The key to generating universal influenza immunity via vaccination is to target functionally-conserved regions of the virus, which include epitopes on the internal proteins for cross-reactive T cell immunity or on the HA stem for broadly reactive antibody responses. In the wake of the 2009 H1N1 pandemic, broadly neutralizing antibodies have been characterized and isolated from convalescent and vaccinated individuals, inspiring development of new vaccination techniques to elicit such responses. Induction of influenza-specific T cell responses through vaccination has also been examined in clinical trials. Strong evidence is available from human and animal models of influenza to show that established influenza-specific T cell memory can reduce viral shedding and symptom severity. However, the published evidence also shows that CD8+ T cells can efficiently select immune escape mutants early after influenza virus infection. Here, we discuss universal immunity to influenza viruses mediated by both cross-reactive T cells and antibodies, the mechanisms of immune evasion in influenza, and how to counteract commonly occurring-escape variants.